Pembekalan mental dan keterampilan pembuatan sabun padat pada anak binaan Panti Asuhan dan Tahfidz Amanah Kaharu Sudiang - Taufiq Dalming; Dedy Ma`ruf (Universitas Mataram, 2021)
Soul provision and skills of making Solid soap for the children assisted by the orphanage and tahfidz amanah Kaharu Sudiang are alternative activities in the context of strengthening the Islamic personality and provision of independence. Activities carried out in the form of demonstrations of making solid soap, mentoring, and watching movies together. The activity received good responses from the assisted children and participated in the activity enthusiastically. This activity became the starting point for similar activities with other themes.